Em busca da complexa simplicidade: o consumo no discurso jornalístico da revista Vida Simples - Reginato, Gisele Dotto (2011)
In this study, we analyse Vida Simples magazine - published monthly by Abril company -, a publication that intends to show an alternative and simpler lifestyle. However, this proposal also involves the issue of consumption and further articulates the dimensions of the individual and the collective in a project that is based on reflexivity. Therefore, the aim of this research is to understand the relationship between consumption and simplicity in the discourse of Vida Simples magazine. To this end, the method used is Discourse Analysis, a theoretical and methodological construction that presents speech as a producer of meanings, from which the subject means himself and others. In the analysis, we found 314 discursive sequences cut of 114 texts, where the reiterations of meaning are grouped into eight paraphrastic families. These paraphrastic families indicate the composition of three discursive formations, which demonstrate that the discourses of Vida Simples magazine are tensioned between the encouragement of individual consumption, of one that considers the environmental and of consumption politicized. That is, all three discursive formations represent ways more or less politicized of understanding the simplicity and consumption, with ideological disputes that are materialized in discourse. Based on the identification of meanings, we understand the ideological formations that discursive formations are linked to, we found the sociocultural aspects that constitute the discourse and we contextualize the meanings found in the magazine, entering the debate on reflexivity and on the individual in contemporary society. Through analysis of the reiterations of sense, especially landslides and interweaving of these senses, we understand there is a hegemonic ideological formation in Vida Simples magazine, which is based on a dominant ideology of our time: that the individual is the measure of everything. The theme of this work is relevant to the research line, Identities Contemporary Media, of the Graduate Program in Communication from UFSM, since it is a study on the role of mediated communication in the construction of social dynamics, and vice versa.